MAIN THEORETICAL POSITIONS OF LINGUOCULTUROLOGY - Dzhangabayeva, G.K. (SCIENCE and SOCIETY, 2026)
The article explores the main theoretical principles of cultural linguistics as an independent discipline at the intersection of linguistics and cultural studies. It examines the fundamental concepts of the interrelation between language and culture presented in the works of W.Von Humboldt, E.Sapir, B.Whorf, A.Wierzbicka, and others. The study emphasizes that language functions not only as a means of communication but also as a vital instrument for preserving and transmitting cultural values. Cultural linguistics is defined as a field that investigates the ways in which culture is reflected in language and how linguistic worldviews are formed.